Uncommon mandibular osteomyelitis in a cat caused by Nocardia africana - de Farias, Marconi Rodrigues; Werner, Juliana; Ribeiro, Márcio Garcia [UNESP]; Rodigheri, Sabrina Marin; Cavalcante, Carolina Zaghi; Chi, Kung Darh; Zeni Condas, Larissa Anuska [UNESP]; Gonoi, Tohru; Matsuzama, Tetsuhiro; Yazama, Katsukiyo (Biomed Central Ltd., 2012)
Background: Nocardiosis is an unusual infection in companion animals characterized by suppurative to pyogranulomatous lesions, localized or disseminated. Cutaneous-subcutaneous, pulmonary and systemic signs are observed in feline nocardiosis. However, osteomyelitis is a rare clinical manifestation in cats. Nocardia cyriacigeorgica (formerly N. asteroides sensu stricto), Nocardia brasiliensis, Nocardia otitidiscaviarum, and Nocardia nova are the most common pathogenic species identified in cats, based on recent molecular classification (16S rRNA gene). The present report is, to our knowledge, the first case of mandibular osteomyelitis in a cat caused by Nocardia africana, diagnosed based upon a combination of methods, including molecular techniques.Case presentation: A one-year-old non-neutered female cat, raised in a rural area, was admitted to the Companion Animal Hospital-PUCPR, Sao Jose dos Pinhais, State of Parana, Brazil, with a history a progressive facial lesion, difficulty apprehending food, loss of appetite, apathy and emaciation. Clinical examination showed fever, submandibular lymphadenitis, and a painless, 8 cm diameter mass, which was irregularly-shaped, of firm consistency, and located in the region of the left mandible. The skin around the lesion was friable, with diffuse inflammation (cellulitis), multiple draining sinuses, and exudation of serosanguinous material containing whitish sulfur granules. Diagnosis was based initially in clinical signs, microbiological culture, cytological, and histopathological findings, and radiographic images. Molecular sequencing of 16S rRNA of isolate allowed diagnosis of Nocardia africana. Despite supportive care and antimicrobial therapy based on in vitro susceptibility testing the animal died.Conclusion: The present report describes a rare clinical case of feline osteomyelitis caused by Nocardia africana, diagnosed based upon a combination of clinical signs, microbiological culture, cytological and histopathological findings, radiographic images, and molecular methods. The use of modern molecular techniques constitutes a quick and reliable method for Nocardia species identification, and may contribute to identification to new species of Nocardia that are virulent in cats.
Keywords: Cat; Nocardia africana; Feline nocardiosis; Osteomyelitis